CREDIT ACCESSIBILITY ON THE FINANCIAL PERFORMANCE OF SMALL & MEDIUM ENTERPRISES (SMES) IN UGANDA. - Nambuya Whitney Gladys (UCU, 2024)
This study was inspired by the barriers that small & medium enterprises face when trying to access credit from commercial banks which is essential for sustaining their business growth and financial performance. The aim of this study is to investigate how credit accessibility affects the financial performance of SMEs in Mukono Central Division. To achieve this, the study was focused on key objectives such as; to examine the relationship between availability of credit and the financial performance of SMEs in Mukono, to examine the relationship between cost of credit and the financial performance of SMEs in Mukono, to examine the relationship between ease of access to credit and the financial performance of SMEs in Mukono. The study used a cross-sectional survey design. For data collection, a closed-ended questionnaire was issued to respondents who were the business owners or managers. A random sample of 52 respondents was drawn from a population of 60 licensed SMEs using simple random sampling method. The data was subjected to descriptive and inferential analyses, including linear regression to determine the relationship among the variables. The findings revealed a significant positive correlation between access to credit and the financial performance of SMEs. To improve credit access for SMEs, it is important for commercial banks and other lending institutions to reconsider the cost of credit, ensuring it aligns with what borrowers can realistically afford.